(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to know the effect of the strategy (Observe, Discuss, Practice, Discuss) on the achievement and future thinking skills of fifth grade science students in chemistry. To achieve the study objective, the researcher followed the experimental design in applying the strategy (Observe, Discuss, Practice, Discuss) on the experimental group and the control group. The research sample consisted of (62) students from Al-Shatrah Preparatory School for Boys, with (31) students in the experimental group who studied according to the strategy (Observe, Discuss, Practice, Discuss) and (31) students in the control group who studied according to the traditional method. The equivalence between them was verified in the variables of age, previous achievement, prior knowledge test, and future thinking skill. An achievement test consisting of (50) items in multiple test items was prepared and presented to a group of arbitrators and experts to ensure the validity of the test. The reliability coefficient of the test was calculated and was (0.885). A future thinking skills test consisting of (6) skills was prepared, and its reliability was verified. The research results showed that the experimental group, which studied according to the (Observe, Discuss, Practice, Discuss) strategy, outperformed the control group, which studied according to the traditional method. 1) There was no statistically significant difference at the significance level of (0.05) in the scores of the experimental group, who studied according to the (Observe, Discuss, Practice, Discuss) strategy, and the average scores of the control group, who studied according to the traditional method, in achieving chemistry. 2) There was no statistically significant difference at the significance level of (0.05) in the scores of the experimental group, who studied according to the (Observe, Discuss, Practice, Discuss) strategy, and the average scores of the control group, who studied according to the traditional method, in the future thinking skills test. The research reached a set of conclusions, recommendations, and proposals